PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Saragi, Dame Ria Rananta; Sianipar, Lasma Lenida Rosinta; Junaidi, Junaidi (Jurnal Ekonomi dan Bisnis (EK&BI), 2024)
Today's business world is very competitive and growing very quickly. When a business grows, its activities towards various resources automatically increase to generate profits. This can affect the environment and create social disparities for parties directly related to the company, society, and the surrounding environment. Therefore, every business action is expected to help the economic growth of stakeholders, including the government, the business world, and society, so that they can benefit each other, contribute to each other, and have a harmonious relationship. As a result, there is an awareness to increase Corporate Social Responsibility (CSR) to reduce negative responses to the company.The aim of this research is to test and analyze the influence of corporate social responsibility on company value. The sample and population used in this research are food and beverage companies in the sub-sector of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The samples were taken using a purposive sampling technique. The data analysis method in this research uses multiple linear regression analysis which is processed using SPSS 21 software. The results of this research prove that CSR has a positive effect on financial value.